2013
DOI: 10.3906/sag-1206-25
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of children with inguinoscrotal ectopic adrenal tissues

Abstract: Weight−length relationships (WLRs) for 28 fi sh species were investigated in an enclosed basin in the Sea of Marmara. Due to low sample sizes (<15), 11 species were not taken into account, but length results were represented. WLR information for 8 species was taken for the fi rst time in the Sea of Marmara, and these 8 species were examined according to sex. Parameters b were found to be insignifi cant between the sexes (P > 0.05). In this study, WLRs for Pomatoschistus marmoratus are presented for the fi rst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Currently, majority of the cases of ectopic adrenal tissue are known to be encountered in the retroperitoneal area, the kidney parenchyma, the celiac plexus, thorax, liver capsule, lungs brain and less often in the spermatic cord, testis and the surrounding tissues (2). In the literature, it has been noted that the majority, primarily in the pediatric age group, are determined incidentally during surgery (1,3). In contrast to the literature, the case presented here is 35 years old.…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…Currently, majority of the cases of ectopic adrenal tissue are known to be encountered in the retroperitoneal area, the kidney parenchyma, the celiac plexus, thorax, liver capsule, lungs brain and less often in the spermatic cord, testis and the surrounding tissues (2). In the literature, it has been noted that the majority, primarily in the pediatric age group, are determined incidentally during surgery (1,3). In contrast to the literature, the case presented here is 35 years old.…”
Section: Introductionmentioning
confidence: 60%
“…They develop in the form of multiple primordial or separately secondary to the main gland. If they are close to the main gland, they include the medulla (1,4). Therefore, the majority of ectopic adrenal tissues seen in the spermatic cord or the epididymis are formed from the cortex section only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 Some cases of EAT have also been reported in girls, although the lower incidence in girls is not easy to explain. Oğuz et al, 12 in a multicenter study, reported an incidence of EAT of 2.02% out of a total of 296 male patients who had inguinoscrotal surgery between 2009 and 2011. Vaos et al 13 reported a comprehensive incidence of 2.5% of EAT in 316 inguinoscrotal operations performed on 289 consecutive patients (0.7% in girls and 1.8% in boys).…”
Section: Discussionmentioning
confidence: 99%